Terawatt Post compression of high energy fs pulses using ionization: A way to overcome the conventional limitation in energy of few optical cycle pulses - Descamps D.; Mével E.; Petit S.; Fourcade-Dutin C.; Dubrouil A.; Hort O.; Constant E. (EPJ Web of Conferences, 2013)
By using optical-field-ionization of helium we postcompress 50 fs pulses to 8 fs with a pulse energy of 8,7 mJ. Hence few cycle pulses were obtained with TW peak power and a good shot-to-shot stability.